2014
DOI: 10.5194/ars-12-241-2014
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing and modeling of lightning caused long recovery events within the lower ionosphere using VLF/LF radio wave propagation

Abstract: Abstract. On the 4 November 2012 at 3:04:27 UT a strong lightning in the midst of the North Sea affected the propagation conditions of VLF/LF transmitter radio signals from NRK (Iceland, 37.5 kHz) and GBZ (UK, 19.58 kHz) received at 5246 • N 8 • E (NW Germany). The amplitude and phase dips show a recovery time of 6-12 min pointing to a LOng Recovery Early VLF (LORE) event. Clear assignment of the causative return stroke in space and time was possible with data from the WWLLN (Worldwide Lightning Location Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The main evidence is the tendency for the LOREs to occur with higher lightning peak current of both positive and negative polarities, which are also known to trigger elves [Haldoupis et al, 2013], whereas sprites are largely associated with positive strokes. Schmitter [2014] reached a similar conclusion theoretically. On the other hand, Kotovsky and Moore [2016] point out that a large number of sprite halos are triggered by negative cloud-to-ground strokes and suggest a different mechanism.…”
Section: Introductionsupporting
confidence: 63%
“…The main evidence is the tendency for the LOREs to occur with higher lightning peak current of both positive and negative polarities, which are also known to trigger elves [Haldoupis et al, 2013], whereas sprites are largely associated with positive strokes. Schmitter [2014] reached a similar conclusion theoretically. On the other hand, Kotovsky and Moore [2016] point out that a large number of sprite halos are triggered by negative cloud-to-ground strokes and suggest a different mechanism.…”
Section: Introductionsupporting
confidence: 63%
“…Its conductivity is primarily determined by (1) the electron density, (2) the electron mobility (inversely related to the electron‐neutral collision rate), and (3) the Earth's magnetic field. In our simplified model, we assumed that all the effects that materially influence ionospheric reflections can be captured in the exponential conductivity profile expressed as follows (Schmitter, ; Wait & Spies, ): σ()h=σ0exp[]β()hh where h is the altitude above ground, h ′ and β are the reference height and the steepness of the electron density profile, and σ 0 = 2.22 μS/m is the conductivity at h = h ′. Note that sometimes h ′ is referred to as the virtual reflection height of the ionosphere for VLF waves.…”
Section: Methodsmentioning
confidence: 88%
“…They found that the apparent ionospheric reflection height, estimated from measured sky wave delays relative to the ground wave, tends to decrease with stroke order within the same flash, at least under daytime conditions. This result (interpreted by the authors as being, at least in part, due to additional ionization associated with elves) is inconsistent with predictions of existing models (e.g., Marshall, ), except for that of Schmitter ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote VLF/LF sensing therefore since decades proves as an inexpensive and reliable way to assess forcing processes in this layer, also with regard to auroral pre- cipitation activity (Cummer et al, 1996(Cummer et al, , 1998. During the last years we have developed a modeling scheme that allows to assess ionospheric forcing parameters from VLF/LF amplitude and phase recordings of distant Minimum Shift Keying (MSK) transmitters (Schmitter, 2010(Schmitter, , 2011(Schmitter, , 2012(Schmitter, , 2013(Schmitter, , 2014. As the amplitude of these transmissions is constant, any observed variations are caused along the propagation path.…”
Section: Introductionmentioning
confidence: 99%